IMPACT OF LACTOBACILLUS PLANTARUM (NCDC LP20) PROBIOTIC BACTERIA ON ENHANCED INNATE IMMUNO PARAMETERS IN LABEO ROHITA (ROHU) - Reddy, S. Janardana; Ali, Subhan (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
In according to several reports, the advantageous effects of bacteria on fish have well been documented. Probiotics as an alternative strategy have been suggested to be used as reinstatement for antimicrobial drugs and growth promoters. Some researchers believe that Probiotics have an advantageous for strengthening the health of fish in aquaculture and augmenting fish performance. The present study was designed to investigate the enhanced effects in innate immunological indices of by the oral administration of probiotic Lactobacillus plantarum (NCDC LP20) in freshwater fish, Labeo rohita (Rohu). Probiotic was administered orally at three different doses 1×106 (T2), 1.5×106 (T3), 2×106 (T4) cfu/g feed to Labeo rohita for four weeks. The positive control group (T1) and negative control group (T5) was fed feed without probiotic for the same period. On 29thday, blood and serum samples were collected to determine differential leukocyte counts (DLC), respiratory burst activity (NBT assay) and serum bactericidal activity. Fishes were challenged intra peritoneal injection with Aeromonas hydrophila after four weeks in the treatment groups (T2, T3 and T4) and also in the positive control group (T1), while the negative control group (T5) was administered with phosphate buffer saline (PBS pH 7.2). The NBT assay and DLC were assessed on 7th day post challenge. Probiotic Lactobacillus plantarum (NCDC LP20) treated fish showed significantly higher (P <0.05) respiratory burst activity and bactericidal activity during the pre-challenge compared with the control groups. The highest respiratory burst activity (0.42±0.01) and serum bactericidal activity was recorded in the group (T4) fed feed containing Lactobacillus plantarum (NCDC LP20) at 2×106 cfu/g feed. Granulocytes numbers were significantly higher (P <0.05) in treatment groups in comparison to the control in both the pre and post challenge periods. The result suggests that Lactobacillus plantarum (NCDC LP20) significantly enhance innate immune response in Labeo rohita (Rohu).